Effect of oxygen hyperbaric therapy on malondialdehyde levels in saliva of periodontitis patients with type 2 diabetes mellitus - Dian Mulawarmanti; Widyastuti Widyastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Lipid peroxidation (LPO) has implication in pathogenesis of several pathological disorders including periodontitis. Malondialdehyde (MDA) is end products of upid peroxidation. Hyperbaric Oxygen Therapy (HBOT) involves the administration of 100% oxygen under atmosphere pressure and has been used as an adjuvant therapy, while saliva is a diagnostic tool for many oral and systemic diseases. Purpose: The aim of this study was to examine the effect of HBOT on malondialdehyde in saliva to measure lipid peroxidation in periodontitis patients with type 2 Diabetes Mellitus (DM). Methods: Eight regulated type 2 DM subjects were compared to ten unregulated periodontitis patients type 2 DM (n = 18). Pre HBOT and after 10 days HBOT with 2.4 ATA dose, unstimulated whole saliva samples from study subjects were collected, centrifuged at 3000 g for 15 minutes and were then stored at −80° C until analyzed. The MDA level was determined with 2-thiobarbituric acid by a colorimetric method at 532 nm. Results: Data showed that regulated type 2 DM had lower level of MDA (3.08 ± 0.62 ug/mol) compared with unregulated periodontally- type 2 DM subjects (5.88 ± 1.04 ug/mol) (p>0.05). MDA levels were significantly lower after HBOT in regulated DM (2.30 ± 0.46 ug/mol) compared with unregulated periodontally type 2 DM (4.09 ± 0.77ug/mol) (p < 0.05). The regulated DM subjects and post HBOT showed MDA levels lower than the periodontally-unregulated group significantly. Conclusion: The saliva of periodontitis patients with unregulated type 2 DM showed more lipid peroxidation than regulated DM type 2. HBOT decreased MDA levels in regulated and unregulated type 2 DM with periodontitis.